PENGARUH PEMBERIAN HAND MASSAGE DENGAN AROMATERAPI LAVENDER DALAM MENURUNKAN STRES KELUARGA PASIEN ICU - Margaretha Kurniastuti (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2025)
The care of family members in the Intensive Care Unit (ICU) is one of the causes of stress in families who are waiting in the hospital. There are various contributing factors such as changes in family roles, the cost of care and critical conditions are one of the causes of stress in families. Families, as medical decision-makers, are expected to be stable and unaffected by excessive stress. Therefore, it is important to find effective ways to assist the patient's family in managing the stress that arises. Complementary therapy such as lavender aromatherapy combined with hand massage is one alternative method in helping to reduce stress in families. This study aims to determine the effect of giving lavender aromatherapy with hand massage in reducing stress in the patient's family in the ICU waiting room. This research is a quasi experimental method with one group test pretest and postest. Respondents in this study were 16 people who were determined using purposive sampling technique. This study used the perceived stress scale 10 (PSS-10) instrument. This research was conducted in one of the private hospitals in Yogyakarta City in January 2023.This study aims to determine the effect of giving lavender aromatherapy with hand massage to the patient's family in the ICU waiting room. This research is a quasi experimental method with one group test pretest and postest. Respondents in this study were 16 people who were determined using purposive sampling technique. This study used the Perceived Stress Scale 10 (PSS-10) instrument. The results of the bivariate analysis test using the Wilcoxon test showed a significant difference in pretest and posttest scores on the provision of hand massage intervention with Lavender aromatherapy (p < 0.005). The conclusion that hand massage intervention with lavender aromatherapy is effective in reducing stress in the patient's family.